Tren Pariwisata Backpacker di Asia Tenggara - Herra Herryani; Agung Yuliyanto Nugroho (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
The backpacker tourism trend in Southeast Asia has grown rapidly in the past few decades, with Thailand becoming one of the top destinations for budget travelers. This study aims to identify the factors that make Thailand a favorite destination for backpackers in the region. The research methodology involves literature analysis, interviews with backpackers, and tourism statistics. The results show that the combination of natural beauty, cultural diversity, affordable cost of living, good tourism infrastructure, and easy access to various attractions are the main factors that attract backpackers. In addition, Thailand's image as a friendly, safe, and open country for foreign tourists also contributes to its popularity. The study also compares Thailand with its neighboring countries such as Vietnam, Cambodia, and Indonesia to understand Thailand's competitive advantages. The findings provide insights for the government and tourism industry players in developing sustainable strategies to maintain and enhance the attractiveness of the destination for the backpacker tourist segment